Harnessing exercise to combat chronic diseases: the role of Drp1-Mediated mitochondrial fission - Sun, Yingxin; He, Junchen; Bao, Lei; Shi, Xiaoming; Wang, Jinghong; Li, Qingwen (Frontiers in Cell and Developmental Biology, 2025)
Enhanced Drp1 activity mediates excessive mitochondrial fission, contributing to the onset and progression of various chronic diseases, including neurodegenerative, cardiovascular, and metabolic disorders. Studies indicate that exercise mitigates mitochondrial dysfunction by modulating Drp1-related signaling targets, thereby inhibiting Drp1 activity and reducing excessive mitochondrial fission. This, in turn, enhances mitochondrial function and cellular metabolism. This review synthesizes the current understanding of Drp1 structure and activation mechanisms, and analyzes the effects of exercise interventions on Drp1-mediated mitochondrial fission in different disease models to improve common chronic conditions. This research deepens our insight into the specific mechanisms of Drp1-induced excessive mitochondrial fission in chronic disease pathogenesis, offering new theoretical support and practical guidance for exercise as a non-pharmacological intervention strategy.